Unveiling Digital Influences: How Social Media Shapes Tourism Behavior in Boek Phrai Community-based Tourism, Ban Pong District, Ratchaburi Province, Thailand - Klaidaeng, Chaisak; Akkapin, Supaphorn; Techajareonvikul, Aswin (Journal of Community Development Research (Humanities and Social Sciences), 2024)
This study examines the impact of social media on tourism dynamics in Boek Phrai Sub-district, Ban Pong District, Ratchaburi Province, Thailand. Using a quantitative approach, data were collected through questionnaires from 400 Thai tourists to evaluate the influence of social media platforms on their travel decision-making. Statistical analyses, including Pearson’s correlation and multiple regression, demonstrate a strong positive correlation between social media awareness and travel intentions, particularly among younger, educated tourists. Key factors influencing travel decisions include the perceived usefulness of social media (β = 0.529), attraction appeal in social media content (β = 0.454), and recognition of travel preparation information (β = 0.279). The findings highlight the critical role of User-generated Content (UGC), social media Word-of-Mouth (WOM), and engaging visuals in shaping tourist behavior. These insights underscore the importance of strategic social media engagement to promote lesser-known destinations like Boek Phrai, Ratchaburi Province, contributing to sustainable tourism and community-based economic growth in Thailand. Keywords: Social Media, Community-Based Tourism, User-generated Content, Decision-Making, Social Media Marketing